Principles of justification of regional programmes of municipal solid waste treatment - Safranov, Tamerlan; Shanina, Tetiana; Prykhodko, Veronika; Shynkarenko, Mykola (Lviv Politechnic Publishing House, 2018)
It is the scientific justification of the regional programme of the municipal solid waste treatment (MSW) with the example of Odessa region which will promote the increase is environmental safety of the population, reduction of the negative impact on the environment by the improvement and modernization of the existing system of MSW treatment with final achievement of a “zero waste” state due to the transfer of the maximum amount of waste into the liquid secondary raw materials, alternative source of energy and environmentally-friendly organic-mineral fertilizer. Such approach differs essentially from the existing developments of regional programmes of MSW treatment and has a scientific - methodical and practical value.
Keywords: municipal solid waste; waste treatment; regional programme